The Importance of Context in a Global World: Three Case Studies from Rural and Remote International Locations - Henderson, Robyn; M. Mandalawi, Sazan (Australian and International Journal of Rural Education, 2024)
Global education is often framed in terms of standardised testing that makes comparisons across nations. This is particularly evident with international measures like the Programme for International Student Assessment (PISA), which tests 15-year-olds in member countries. Images on the PISA website provide representations of education that seem to clash with some of the contexts where we have conducted research. This prompted an investigation into educators’ talk about local contextual realities, and how—or whether—they were impacted by global calls for quality education. The study focused on three different educational programs: education for adolescent girls in a refugee camp in the Kurdistan Region of Iraq, school education in a western Queensland rural/remote town in Australia, and the Migrant Education Program in rural Illinois in the United States. The data were collected through semi-structured interviews and field observations. Following data analysis, three case study narratives were constructed. A final step of analysis identified four shared pillars that made learning in rural and remote areas impactful and effective: context relevance, educators’ openness to learning, flexibility of teaching/learning approaches, and responsiveness to learners’ needs. The data demonstrated that the educators had a broader picture—national or global—in mind, but their main aim was to provide learning opportunities that were responsive, flexible and contextually appropriate to their location.